Peasants and land tenure in the Peruvian highlands in the transition from the Colony to the Republic - Jacobsen, Nils (1991)
The main paradox of the land tenure regime in the name of the Altiplano during the latter part of the colonial period was the following: land was cheap. It had not yet become a "commodity good", since in principle it was marketed as a secondary part of the livestock capital it fed. In most of the transactions the value of the cattle and that of their pastures was one. Without the cattle the pastures were worth very little. This corresponded to a situation in which both livestock and population were not numerous.